2016
DOI: 10.1007/s10086-016-1582-3
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of fiberboard containing lingo-cellulose nanofiber made from wood fibers

Abstract: Wood-based materials are fabricated with adhesives composed of various materials derived from fossil fuels. It is difficult to identify replacements for these chemical adhesives. This study explored nanofiber technologies as an alternative to these adhesives. In this study, we focused on reinforcement effects of lingo-cellulose nanofiber (LCNF) on fiberboards made from softwood and hardwood fiber. We discuss the density effects of reinforcement with LCNF because the density of mediumdensity fiberboard (MDF), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Addition of CNF showed the hot water resistance, but the improvement was observed in adhesive with CNC. Investigations were done on reinforcing effect of lingo-cellulose nanofiber (LCNF) in fiberboards made from softwood and hardwood fiber [61]. Compared with the control fiberboard, IB for LCNF-mixed fiberboard was higher.…”
Section: Modification Of Wood Adhesives With Nanocellulosementioning
confidence: 99%
“…Addition of CNF showed the hot water resistance, but the improvement was observed in adhesive with CNC. Investigations were done on reinforcing effect of lingo-cellulose nanofiber (LCNF) in fiberboards made from softwood and hardwood fiber [61]. Compared with the control fiberboard, IB for LCNF-mixed fiberboard was higher.…”
Section: Modification Of Wood Adhesives With Nanocellulosementioning
confidence: 99%
“…A similar study on the evaluation of binding effects in wood flour board containing lingo cellulose nanofibers showed a significant enhancement of physical and mechanical properties of the board [42]. The study focused on reinforcement effects of lingo-cellulose nanofiber on fiberboards made from softwood and hardwood fiber was conducted [82]. In the study reinforcement effects of lingo-cellulose nanofiber on fiberboards was observed, due to close binding between lingo-cellulose nanofiber and wood fibers.…”
Section: Nanocellulose Application In Wood Adhesivesmentioning
confidence: 93%
“…Such approach ele-gantly highlights the use of the amphiphilic nature of lignocellulosic hybrid particles in two possible applications, i.e., emulsions and composites. Other important applications include adhesives, 410 superhydrophobic coatings, 411 oil barrier coating, 412 nanopapers, 413 and others.…”
Section: Carbon-lignin Hybridsmentioning
confidence: 99%
“…, emulsions and composites. Other important applications include adhesives, 410 superhydrophobic coatings, 411 oil barrier coating, 412 nanopapers, 413 and others.…”
Section: Lignin-based Nanohybridsmentioning
confidence: 99%